Emotional Intelligence -A Key Factor for Solving Social Issues o Employees with Reference to Indian BPOs - Priyadarsini, P.; Maran , K (Gyan Management Journal, 2012)
India is all set to register the highest growth rate in the call center services industry operating in Asia Pacific Region. According to the report published by National Association of Software and Servi companies (NASSCOM) India’s call center industry accounts for a quarter of the country’s software a service exports. On the other side BPO employees face problems in their family life due to odd workir hours which has an impact on their physical, social and emotional wellbeing. The divorce rate in Ind about twenty years ago was about 5 percent. Now, the divorce rate is about 12.5 percent. This rate,. recent years, has increased tremendously, SO percent of the cases belonged to BPO employees. Due the nature of work, family life gets disrupted and communication among the family members g affected. The advocates have pointed out that the divorce rates are threefold when either of the coup works on night shifts This paper aims to analyze the problems of BPO employee on the roots of the· Emotional Intelligence. The study was carried out in Chennai with a sample size of 450 BPO employe The study focuses on the social support and Emotional Intelligence dimensions of BPO employee.. Multiple regression, factor analysis and chi-square tools have been applied to analyse the hypothesL. The study employed Trait Emotional Intelligence Questionnaire to measure El, and Multidimension Scale of Perceived Social Support (Zimet, et al, 1988) to analyze the social support received from family,friends and society.